Why to outline the limitations of the study? - Raidell Avello Martínez; Mabel A. Rodríguez Monteagudo; Pavel Rodríguez Monteagudo; Dailyn Sosa López; Bárbara Companioni Turiño; Rodrigo Leandro Rodríguez Cubela (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Expressing the limitations of a study, in spite of being an important issue in scientific articles, is a task which most authors tend to avoid. This is the reason why, most published research are lacking this information. Although the responsibility about this phenomenon is the author's, it is also reviewers' duty to promote and demand that limitations of the research they review are reported. These may be of a methodological type or be related to the researcher. It is necessary to perceive them as an opportunity, even the limitations of a study could encourage other researchers for new works.